Functional characterization of 10 CYP4A11 allelic variants to evaluate the effect of genotype on arachidonic acid ω-hydroxylation - Saito, Takahiro; Honda, Masashi; Takahashi, Masamitsu; Tsukada, Chiharu; Ito, Miyabi; Katono, Yuki; Hosono, Hiroki; Saigusa, Daisuke; Suzuki, Naoto; Tomioka, Yoshihisa; Hirasawa, Noriyasu; Hiratsuka, Masahiro (Drug metabolism and pharmacokinetics, 2015)
Genetic variations in cytochrome P450 4A11 (CYP4A11) contributes to inter-individual variability in the metabolism of fatty acids such as arachidonic acid. CYP4A11 metabolizes arachidonic acid to 20-hydroxyeicosatetraenoic acid (20-HETE), which is important for the regulation of blood pressure. Polymorphisms in CYP4A11 are associated with susceptibility to hypertension. In this study, we evaluated the in vitro ω-hydroxylation of arachidonic acid by 10 CYP4A11 allelic variants, which cause amino acid substitutions in the encoded proteins. CYP4A11 variants were heterologously expressed in COS-7 cells and the kinetic parameters of arachidonic acid ω-hydroxylation were estimated. Among 10 CYP4A11 variants, 5 (CYP4A11-v1, CYP4A11-v2, CYP4A11-v3, CYP4A11-v4, and CYP4A11-v7) showed no or markedly lower activity compared to wild-type CYP4A11. This functional analysis of CYP4A11 variants could provide useful information for the effective prevention and treatment of hypertension.